Prevalence of SARS-CoV-2 Specific Antibodies in Asymptomatic Hemodialysis Patients. (19th May 2022) - Etemadi, Jalal; Bordbar, Shima; Soltani-Zangbar, Mohammad Sadegh; Hajivalili, Mahsa; Aghebati-Maleki, Leili; Motavalli, Roza; Mahmoodpoor, Ata; Shahmohammadi-Farid, Sima; Abedi Azar, Sima; Niknafs, Bahram; Roshangar, Leila; Babaloo, Zohreh; et al.
ABSTRACT: Background: Since the outbreak of the new coronavirus pandemic, the importance of carrying out an infection check to prevent acquisition and transmission among end-stage renal disease patients (ESRD) under maintenance hemodialysis (MHD) has become a major concern in the health care system. Applying serology screening tests could enlighten the view with regards to disease prevalence in dialysis wards. Methods: We subjected 328 end-stage renal disease patients to maintenance hemodialysis. After dividing patients into suspicious and non-suspicious groups for COVID-19 infection based on their clinical manifestation, they were investigated for SARS-CoV-2 specific IgM and IgG screening against nucleoprotein (NP), spike protein (SP), and receptor-binding domain (RBD), utilizing our recently developed ELISA tests. Results: We found that approximately 10.1% of asymptomatically tested cases were antibody positive. Although IgG positivity showed a higher prevalence than IgM across all three virus antigen subunits, there were no significant differences among mentioned immunoglobulins of the studied groups. The most prevalent antibody was from the IgG subtype against virus nucleoprotein (NP), while the lowest prevalence was attributed to receptor-binding domain (RBD) IgM. Conclusion: High seropositive rate among asymptomatic end-stage renal disease patients, as a sample of high-risk population, reflected the importance of considering SARS-CoV-2 specific antibody screening for disease containment.